(untitled) (SCIÉNDO INGENIUM, 2021)
Factorial design allows the elaboration, selection and determination of a vaccine strain of enteric Salmonella Serotype Enteritidis 82139 with validation of dsbA, dle and dlp gene function with respect to mobility capacity and intracellular bacterial invasion due to Minimum Significant Difference (DMS) and with 99% of confidence level for mobility and 95% for bacterial intracellular invasion. Results at 0.025 DMS and significantly different, Dle, does show invasiveness in MDCK at 1 hour of bacterial-host cell interaction, intracellular adherence-internalization phase. Dlp, highly homologous protein, capable of complementing dsbA- mutation. Dle, it presents specific and limited function. In the absence of DsbA and Dlp, its invasive capacity decreases at the 1st, 2nd and 4th hours of bacterial interaction. DsbA is decisive in the 1st hour of interaction; Dlp of plasmid location has complementary activity to DsbA, with a higher activity potential at 4th hour. In the absence of DsbA, Dlp and Dle, S. enteritidis significantly loses its virulence capacity, an interrelated function under the same pathway, which are reoxidized by DsbB oxidatively. Say, it has no function in mobility. Salmonella ente-ritidis 82139 2C, lacking dsbA and dlp, is a genetic resource for the vaccine strain and 82139 2CI will require future research.